Course of Tuberculosis in Combination with Arterial Hypertension - Khasanova M.F; Farkhadovna, Khasanova Mohira (Research Parks Publishing LLC, 2022)
Tuberculosis in combination with other diseases is more severe. Tuberculosis is one of the oldest insidious diseases. Tuberculosis affects not only the lungs, but also all organs and systems. Currently, against the backdrop of an extremely high prevalence of arterial hypertension (AH) among the population, there is a steady tendency to an increase in the proportion of persons in the structure of hypertension in combination with tuberculosis. The prevalence of hypertension among people over the age of 30 varies from 3.4% to 40.7% [1,2]. The age of onset of hypertension, which was previously considered only for adults, has decreased significantly, and hypertension is registered in earlier age groups [3,4].